2009
DOI: 10.3322/caac.20038
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide Variations in Colorectal Cancer

Abstract: Previous studies have documented significant international variations in colorectal cancer rates. However, these studies were limited because they were based on old data or examined only incidence or mortality data. In this article, the colorectal cancer burden and patterns worldwide are described using the most recently updated cancer incidence and mortality data available from the International Agency for Research on Cancer (IARC). The authors provide 5-year (1998-2002), age-standardized colorectal cancer i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
795
0
32

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,079 publications
(869 citation statements)
references
References 43 publications
9
795
0
32
Order By: Relevance
“…Colorectal cancer remains one of the major causes of cancer deaths worldwide 1, 2. Despite recent advances in the development of various diagnostic tools, in many patients, colorectal cancer is still diagnosed at an advanced stage, and recurrent tumors are often detected even after curative surgery.…”
mentioning
confidence: 99%
“…Colorectal cancer remains one of the major causes of cancer deaths worldwide 1, 2. Despite recent advances in the development of various diagnostic tools, in many patients, colorectal cancer is still diagnosed at an advanced stage, and recurrent tumors are often detected even after curative surgery.…”
mentioning
confidence: 99%
“…5 Depending on the cell type, TRAIL induces apoptosis independently of p53. 4 Therefore, TRAIL promises to be also effective in CRC despite the high rate of mutated p53 in CRC cells.…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that Bthe westernized lifestyle^of physical inactivity, poor diet, obesity, and increased alcohol consumption and longterm smoking attribute to this higher burden [4,5]. In contrast, registries in Asia, Africa and South America have some of the lowest rates of CRC [4].…”
mentioning
confidence: 99%
“…It is thought that Bthe westernized lifestyle^of physical inactivity, poor diet, obesity, and increased alcohol consumption and longterm smoking attribute to this higher burden [4,5]. In contrast, registries in Asia, Africa and South America have some of the lowest rates of CRC [4]. A review of the 12 population based cancer registries from India (Benaguluru, Barshi, Bhopal, Chennai, Delhi, Mumbai, Ahmedabad, Karunagappally, Kolkata, Nagpur, Pune and Thiruvananthapuram) again demonstrated that the incidence of colon and rectal cancer is significantly lower in India for both genders when compared to the West.…”
mentioning
confidence: 99%
See 1 more Smart Citation